Les conflits dans les réseaux de distribution : le cas de l’assurance dommages en France - Venard, Bertrand (Assurances, 1996)
Insurance companies are a long way from being ideal organizations. A multiple of conflicts can appear between members from different networks: employer/employee, order makers/suppliers, firm/distributors, ... The relationship between the company and insurance distributors is an example of a relationship which can become conflictual. It is therefore primordial to find out what causes these conflicts. In order to do this, we propose to make use of a case study which will enable us to build upon an explanatory model.